The effect of personalized versus standard patient protocols for radiostereometric analysis (RSA). Issue 2 (May 2018) - Muharemovic, O.; Troelsen, A.; Thomsen, M.G.; Kallemose, T.; Gosvig, K.K.
Abstract: Introduction: Increasing pressure in the clinic requires a more standardized approach to radiostereometric analysis (RSA) imaging. The aim of this study was to investigate whether implementation of personalized RSA patient protocols could increase image quality and decrease examination time and the number of exposure repetitions. Methods: Forty patients undergoing primary total hip arthroplasty were equally randomized to either a case or a control group. Radiographers in the case group were assisted by personalized patient protocols containing information about each patient's post-operative RSA imaging. Radiographers in the control group used a standard RSA protocol. Results: At three months, radiographers in the case group significantly reduced (p < 0.001) the number of exposures by 1.6, examination time with 19.2 min, and distance between centrum of prosthesis and centrum of calibration field with 34.1 mm when compared to post-operative (baseline) results. At twelve months, the case group significantly reduced (p < 0.001) number of exposures by two, examination time with 22.5 min, and centrum of prosthesis to centrum of calibration field distance with 43.1 mm when compared to baseline results. No significant improvements were found in the control group at any time point. Conclusion: There is strong evidence that personalized RSA patient protocols have a positive effect on image quality and radiation dose savings. Implementation of personal patient protocols as a RSA standard will contribute to the reduction of examination time, thus ensuring a cost benefit for department and patient safety. Highlights: RSA x-ray is demanding technique resulting in high percentage of exposure repetition. Personalized RSA patient protocol increase image quality. Personalized RSA patient protocol contributed to radiation dose savings. RSA X-ray examination time reduces.